THE EFFECT OF GOVERNMENT EXPENDITURE ON EDUCATION, HEALTH SECTOR, AND GROSS REGIONAL DOMESTIC PRODUCT ON HUMAN DEVELOPTMENT INDEX - Al Fian, Muhammad Ilham N.; Bintoro, Nugroho Suryo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The pursuit of social welfare stands as a paramount objective of any given nation, with the underlying social system playing a pivotal role in its realization. To effectively achieve this goal, governments must enhance human well-being, exemplified by increased investments in education and healthcare. These domains inherently contribute significantly to the amelioration of human quality, subsequently leading to the augmentation of overall societal welfare. The focal point of this study is to ascertain the impact of governmental expenditures on education, healthcare, and the gross regional domestic product on the general populace's well-being, as gauged by the Human Development Index (HDI). The empirical data employed for this study comprises secondary data procured from pertinent sources such as the Ministry of Finance, the Indonesian Central Bureau of Statistics, the Ministry of Health, and the Ministry of Law and Human Rights. This research constitutes a quantitative inquiry encompassing 29 regencies and 9 cities situated in East Java during the 2015-2019 timeframe. The analytical approach employed herein hinges on panel data regression analysis.